Characteristics and outcomes of referrals to CAMHS for children who are thinking about or attempted suicide: A retrospective cohort study in two Scottish CAMHS - Gilmour, Lynne; Best, Catherine; Duncan, Edward; Maxwell, Margaret (Frontiers in Psychiatry, 2022)
Suicide among children and young people (CYP) is a leading cause of death. In the UK children identified as suicidal are referred to Child and Adolescent Mental Health Services (CAMHS) for assessment and treatment. However, the number of children referred for suicidality, and their care journey is unknown. This retrospective cohort study conducted in two distinct CAMHS teams, in Scotland, UK, aimed to quantify the numbers of children referred for suicidality, describing this population and the outcomes of these referrals. All CAMHS referrals (n=1159) over a six-month period (Jan-June 2019) were screened to identify those referred primarily for suicidality. Data extracted included: age, gender, source of referral, reason for referral including underlying issues, whether offered an assessment, and referral outcome. Area based deprivation scores were attached to each referral. Associations between the referred CYP’s characteristics (including source of referral and underlying issues) and referral outcomes were explored using Chi Square, Fishers Exact test, and one-way ANOVA. Referrals for 284 children were identified as being for suicidality across the two sites (Site A n=104; Site B n=180). These represented 25% of all referrals to these CAMHS over a six-month period. One third of these concerned children under 12. The underlying issues, referrals sources, and demographic indicators were similar in both sites. In site A 31% were offered an assessment, whilst in Site B which had a dedicated team for suicidal CYP, 82% were offered an assessment. Similarly, more children in Site B were offered treatment (47.8%), than Site A (7.7%). Referrals from A&E were prioritised in both areas, and those who had attempted suicide offered an assessment more often. Older children were more likely to be offered treatment, although they were more likely to present with a history of self-harming behaviour and/or previous suicide attempt. There are high numbers of children being referred to CAMHS for suicidality, and many are young children (<12). There is variation within and between services in terms of assessment, referral outcomes and care pathways for these children. Having a dedicated team to respond to referrals for suicidality appears to support access to assessment and treatment.